DNA Methylation Data-Based Classification and Identification of Prognostic Signature of Children With Wilms Tumor - Tang, Fucai; Lu, Zeguang; Lei, Hanqi; Lai, Yongchang; Lu, Zechao; Li, Zhibiao; Tang, Zhicheng; Zhang, Jiahao; He, Zhaohui (Frontiers in Cell and Developmental Biology, 2021)
Background: As an epigenetic alteration, DNA methylation plays an important role in early Wilms tumorigenesis and is possibly used as marker to improve the diagnosis and classification of tumor heterogeneity. Methods: Methylation data, RNA-sequencing (RNA-seq) data, and corresponding clinical information were downloaded from the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) database. The prognostic values of DNA methylation subtypes in Wilms tumor were identified. Results: Four prognostic subtypes of Wilms tumor patients were identified by consensus cluster analysis performed on 312 independent prognostic CpG sites. Cluster 1 showed the best prognosis, whereas Cluster 2 represented the worst prognosis. Unique CpG sites identified in Cluster 1 that were not identified in other subtypes were assessed to construct a prognostic signature. The prognostic methylation risk score was closely related to prognosis, and the area under the curve (AUC) was 0.802. Furthermore, the risk score based on prognostic signature was identified as an independent prognostic factor for Wilms tumor in univariate and multivariate Cox regression analyses. Finally, the abundance of B cell infiltration was higher in the low-risk group than in the high-risk group, based on the methylation data. Conclusions: Collectively, we divided Wilms tumor cases into four prognostic subtypes, which could efficiently identify high-risk Wilms tumor patients. Prognostic methylation risk scores that were significantly associated with the adverse clinical outcomes were established, and this prognostic signature was able to predict the prognosis of Wilms tumor in children, which may be useful in guiding clinicians in  therapeutic decision-making. Further independent studies are needed to validate and advance this hypothesis.